2014
DOI: 10.1039/c3cc46336b
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the electronic origin of anion order in CrO2−xFx

Abstract: Electron-diffraction and high-resolution lattice images reveal superstructure stripes with wave vectors of (1/3, 0, 1/3) and (-1/3, 0, 1/3), which are associated with the ordered arrangement of F(-). Charge density distribution suggests that these stripes manifest themselves electronically as F(-)-Cr(3+)-F(-) zigzag chains, driven by the anisotropic charge interaction of F(-) anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 21 publications
3
82
0
Order By: Relevance
“…The average differential charge (Bader charge analysis [32]) localized on the Cr ions in the F-Cr-F atom chain are 2.494e rather than 3 in expected, because the magnetization associated with the Cr atom in the F-Cr-F atom chain is quite diffuse due to the magnetic double-exchange interaction. This phenomenon is agreed with the experimental result for F-doped CrO 2 , since high-resolution XPS suggests the mixed-valance feature of Cr 4 þ and Cr 3 þ in the compound [13], and is also observed in calculation of substituting Nb impurity for Cr in CrO 2 [5].…”
Section: Systemsupporting
confidence: 88%
See 2 more Smart Citations
“…The average differential charge (Bader charge analysis [32]) localized on the Cr ions in the F-Cr-F atom chain are 2.494e rather than 3 in expected, because the magnetization associated with the Cr atom in the F-Cr-F atom chain is quite diffuse due to the magnetic double-exchange interaction. This phenomenon is agreed with the experimental result for F-doped CrO 2 , since high-resolution XPS suggests the mixed-valance feature of Cr 4 þ and Cr 3 þ in the compound [13], and is also observed in calculation of substituting Nb impurity for Cr in CrO 2 [5].…”
Section: Systemsupporting
confidence: 88%
“…2 , respectively, for each supercell. Such a longrange F-Cr-F zigzag chain along the 111 〈 〉 direction has been observed in electron-diffraction and high-resolution lattice images [13]. During relaxation, both the external (lattice constants and including angles) and internal (atomic coordinates) parameters are allowed to relax fully.…”
Section: Calculation Methods and Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, anion ordering between O 2− and F − ions appeared in the electron diffraction patterns of CrO 2−x F x with x = 0.1, 0.12, and 0.14. 31 In contrast, because the X-ray scattering factors of O 2− and F − ions are similar to each other in this study, such anion ordering is not observed in the XRD measurements.…”
Section: Resultsmentioning
confidence: 42%
“…Here, CrO 2−x F x , which has a rutile (tetragonal) structure with the P4 2 /mnm space group, exhibits ferromagnetic behavior above room temperature and is regarded as a promising spintronic material because of its nearly 100% spin polarization at the Fermi level. 3,[29][30][31][32] To the best of our knowledge, the electrochemical properties of CrO 2−x F x including CrF 2 have never been reported, except for amorphous CrO 2−x compounds with 0 ≤ x ≤ 0.5. 33 Here, the CrO 2−x F x samples demonstrated a Q recha of 100-400 mA h g −1 at 298 K and a Q recha of 600-700 mA h g −1 at 318 K. The structural, magnetic, and electrochemical properties as a function of x in CrO 2−x F x are discussed in detail.…”
Section: Introductionmentioning
confidence: 98%